Morphology of puparia of flesh flies in Thailand - C. Samerjai (2018)
Puparia of five flesh fly species were investigated for forensic study. Boettcherisca nathani (Lopes, 1961), Boettcherisca peregrina (Robineau-Desvoidy, 1830), Lioproctia pattoni (Senior-White, 1924), Liopygia ruficornis (Fabricius, 1794) and Parasarcophaga (Liosarcophaga) dux (Thomson, 1869) were examined with a scanning electron microscopy (SEM). Differences between species were found in the number and arrangement of papillae in the anterior spiracle, the shape of intersegmental spines between the prothorax and mesothorax and the pattern of spiracular tufts at the posterior spiracle. The anterior spiracle of B. nathani had two rows, comprising 21-27 papillae; while those of B. peregrina and L. pattoni had one or two irregular rows with 24-26 and 20-28 papillae, respectively. Anterior spiracle of L. ruficornis and P. dux had one row of 10-15 papillae. Intersegmental spines between the prothorax and mesothorax and pattern of spiracular tufts at the posterior spiracle are morphologically different. L. ruficornis and P. dux puparia are similar, but the position of the interslit plate between the inner and middle spiracular slits was found to be an important attribute to separate both species. Morphometric analysis on the length and width of puparia of these species revealed statistically different among them. The key for identifying puparia of forensically important flesh flies has been provided.